2017
DOI: 10.1038/ncomms15317
|View full text |Cite|
|
Sign up to set email alerts
|

Free-standing supramolecular hydrogel objects by reaction-diffusion

Abstract: Self-assembly provides access to a variety of molecular materials, yet spatial control over structure formation remains difficult to achieve. Here we show how reaction–diffusion (RD) can be coupled to a molecular self-assembly process to generate macroscopic free-standing objects with control over shape, size, and functionality. In RD, two or more reactants diffuse from different positions to give rise to spatially defined structures on reaction. We demonstrate that RD can be used to locally control formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 36 publications
1
76
0
2
Order By: Relevance
“…Applying mechanical force most likely leads to the breakage of hydrogen bonds and other non‐covalent interactions between molecules of HA 3 in fibers stretching across the interface. Additionally, we confirmed our hypothesis of cross‐interface fiber formation using a reaction diffusion model for this system . The model showed that, indeed, if two compartments with H and A are in direct contact, the gelator HA 3 will form supramolecular fibrils across and on both sides of the interface (Figure b).…”
Section: Figuresupporting
confidence: 80%
See 2 more Smart Citations
“…Applying mechanical force most likely leads to the breakage of hydrogen bonds and other non‐covalent interactions between molecules of HA 3 in fibers stretching across the interface. Additionally, we confirmed our hypothesis of cross‐interface fiber formation using a reaction diffusion model for this system . The model showed that, indeed, if two compartments with H and A are in direct contact, the gelator HA 3 will form supramolecular fibrils across and on both sides of the interface (Figure b).…”
Section: Figuresupporting
confidence: 80%
“…Instead, a white, non‐transparent band was created around the contact point. This band was an indication of HA 3 formation . Previous analysis of this opaque supramolecular gel has shown that this material is made up of bundled fibers that consist largely (>95%) of HA 3 molecules .…”
Section: Figurementioning
confidence: 72%
See 1 more Smart Citation
“…An entirely different method for spatial differentiation is by reaction diffusion, and this is an example where the worlds of MHGs and SHGs meet. Controlled reaction and diffusion of SHG gelator precursors can lead to SHG object and pattern formation,26d,28 as well as the stabilization of emulsions, typically on timescales of hours to days depending on diffusion lengths. Diffusion is often carried out inside an MHG, leading to the formation of MHG–SHG interpenetrated network hybrid gel materials.…”
Section: Supramolecular or Macromolecular Functional Hydrogels?mentioning
confidence: 99%
“…For instance, the employment of self‐assembly systems that are sensitive to external stimuli such as light, enzymatic action, pH, and nucleation seeds, has led to DMSA by controlling the spatial distribution of these stimuli. Another example of DMSA is achieved by reaction‐diffusion, i.e., molecular reactants are separately distributed in space and allowed to react after meeting by diffusion, leading to local self‐assembly at a certain preprogrammed location. Despite the recent progress, a major challenge for further advance lies in control of the spatial parameters of the self‐assembled structures …”
mentioning
confidence: 99%